OPTIMASI RECTIFIER UNTUK MENINGKATKAN KINERJA SERVER PADA PT.GARUDA MEDIA TELEMATIKA - Firman Masykur Arianto; Davan Dwi Maulana; Awanis Hadyan Zulfahmi (Universitas Hasyim Asy`ari, 2024)
This research investigates the performance of the EPS75-4815AF rectifier in maintaining stable power for servers. The efficient implementation of rectifiers can help prevent overheating, ensure network stability, and optimize energy usage. The study employs real-time monitoring, power distribution evaluation, and device replacement with higher efficiency. The findings indicate that rectifiers with larger capacities and efficient cooling systems offer more stable and effective results. Regular maintenance and proper device layout design that promotes optimal air circulation are also significant factors for success in server power stability. This research emphasizes the importance of rectifiers in converting AC to DC power for servers and highlights methods for improving their performance to enhance power stability and optimize energy efficiency.